Analysis of enamel development using murine model systems: approaches and limitations - Pugach, Megan K.; Gibson, Carolyn W. (Frontiers in Physiology, 2014)
A primary goal of enamel research is to understand and potentially treat or prevent enamel defects related to amelogenesis imperfecta (AI). Rodents are ideal models to assist our understanding of how enamel is formed because they are easily genetically modified, and their continuously erupting incisors display all stages of enamel development and mineralization. While numerous methods have been developed to generate and analyze genetically modified rodent enamel, it is crucial to understand the limitations and challenges associated with these methods in order to draw appropriate conclusions that can be applied translationally, to AI patient care. We have highlighted methods involved in generating and analyzing rodent enamel and potential approaches to overcoming limitations of these methods: 1) generating transgenic, knockout and knockin mouse models, and 2) analyzing rodent enamel mineral density and functional properties (structure, mechanics) of mature enamel. There is a need for a standardized workflow to analyze enamel phenotypes in rodent models so that investigators can compare data from different studies. These methods include analyses of gene and protein expression, developing enamel histology, enamel pigment, degree of mineralization, enamel structure and mechanical properties. Standardization of these methods with regard to stage of enamel development and sample preparation is crucial, and ideally investigators can use correlative and complementary techniques with the understanding that developing mouse enamel is dynamic and complex.